1996
DOI: 10.1209/epl/i1996-00564-y
|View full text |Cite
|
Sign up to set email alerts
|

Optical emission in periodic dielectrics

Abstract: PACS. 32.70Cs -Oscillator strengths, lifetimes, transition moments. PACS. 32.80Pj -Optical cooling of atoms; trapping. PACS. 42.50Lc -Quantum fluctuations, quantum noise, and quantum jumps.Abstract. -We show rigorously that the coefficient for spontaneous emission of an atom placed in a dielectric is proportional to the local radiative density of states -that is only a part of the local density of the eigenmodes of the Maxwell equations. Spontaneous emission is inhibited if the atom is located at a position wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
209
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(212 citation statements)
references
References 12 publications
3
209
0
Order By: Relevance
“…16,17 Generally, the dipole moment u 0 is determined by the electronic structures of molecules, which is subject to the influence of local electronic or chemical interactions with a microscopic background. Thus it becomes a function of the emission photon frequency as well as the molecular position.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Generally, the dipole moment u 0 is determined by the electronic structures of molecules, which is subject to the influence of local electronic or chemical interactions with a microscopic background. Thus it becomes a function of the emission photon frequency as well as the molecular position.…”
Section: Resultsmentioning
confidence: 99%
“…The radiative decay rate of a single QD inside the PCM is governed by the projected local density of optical states ͑LDOS͒. 8 In order to probe variations herein, we investigate ensembles of QDs since in this case any dependence on the property of individual QDs is averaged out. Furthermore, QD ensembles provide good signal-to-noise ratio in the measurements and are important for large-volume applications such as PC lasers, LEDs, or solar cells.…”
Section: Decay Dynamics Of Quantum Dots Influenced By the Local Densimentioning
confidence: 99%
“…From these results, it can be concluded that the emission rate strongly depends on the location of the source and on the frequency of the emitted light: emission enhancement as well as emission suppression can be observed. Even if the PhC has no PBG, the emission of a point source can be almost completely suppressed [2]. Figure 2 also shows the results of the energy emitted by a point source embedded in the PhC with d 0:96a, a PhC having a PBG.…”
Section: 120401 (2006) P H Y S I C a L R E V I E W L E T T E R S mentioning
confidence: 98%
“…Already in 1946, it was noticed that spontaneous emission can be controlled with cavity structures [1]. Theoretically, the spontaneous-emission rate can be obtained from Fermi's golden rule containing the local radiative density of states (LRDOS) [2]. For relatively simple cavity structures, the modification of the spontaneous-emission rate can be calculated analytically using either a classical [3][4][5][6][7][8] or a quantum mechanical approach [9].…”
mentioning
confidence: 99%